2005
DOI: 10.1111/j.1523-1755.2005.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcification inhibitors in the pathogenesis of vascular calcification in chronic kidney disease (CKD)

Abstract: These data demonstrate that fetuin-A, OPG, and MGP play an important role in the pathogenesis of uremic vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
262
3
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(295 citation statements)
references
References 51 publications
(44 reference statements)
18
262
3
12
Order By: Relevance
“…The increased incidence of cardiovascular events in patients with CKD is related to both traditional and nontraditional cardiovascular risk factors 2. Nontraditional cardiovascular risk factors include uremia‐related factors, inflammation, and abnormal metabolism of calcium and phosphate 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…The increased incidence of cardiovascular events in patients with CKD is related to both traditional and nontraditional cardiovascular risk factors 2. Nontraditional cardiovascular risk factors include uremia‐related factors, inflammation, and abnormal metabolism of calcium and phosphate 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…High osteoprotegerin values have also been linked to poor glycemic control58, 59 and severity of diabetic nephropathy 60, 61. In patients with chronic renal failure, levels of osteoprotegerin are higher compared with healthy controls,62 are inversely correlated with glomerular filtration rate,63 and correlate with time on maintenance hemodialysis in patients with end‐stage renal disease 64. Third, associations of osteoprotegerin may be attenuated because of the dominance of other factors more relevant to CVD risk in high‐risk patients, including highly prevalent traditional CVD risk factors as well as factors related to quality of clinical care, treatment response, or medication adherence 65.…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental studies have shown a direct association between increase of bone resorption, release of the calcium-phosphate-fetuin-MGP complex, and arterial calcifications [12]. Thus, the fetuin-A and MGP inhibition of extraosseous and, specifically, arterial calcifications is probably exerted locally in the soft tissues and can be somehow impaired in cases of high bone turnover and consequent increase of the mineral-containing complexes in the blood [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular calcifications are of frequent occurrence in uremic subjects, and it is assumed that they greatly contribute to the increased cardiovascular mortality both in conservative and hemodialysis (HD) stages of uremia [1,2]. Several risk factors of vascular calcifications have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation